SCIENTIFIC BASIS OF THE ORGANISATION OF PUBLIC-PRIVATE PARTNERSHIP - Morozova, Lyubov; Khavanova, Natalya; Vetrova, Ekaterina; Sulyagina, Julia (Revista Inclusiones, 2020)
The evolution of the relationship between public government institutes and entrepreneurship in developed and developing countries at various stages of the economy has shown that their constructive interaction is a key factor of successful socioeconomic progress. The ever-growing gap between popular needs and demands for social services and infrastructure and budget constraints have promoted the establishment of partnership between the government and entrepreneurial structures. As the role of the state transforms, this brings more focus on finding alternatives to direct regulation of economic processes.